Variables Affecting Fiscal Stress in Regency/City of Aceh Province 2016-2019 Period - Dina Puspitorini; Lenggogeni Lenggogeni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of Local Goverment Revenue(PAD), Balancing Funds, Other Legitimate Income and Capital Expenditures on Fiscal Stress. The population in this study are all districts and cities in Aceh Province, as many as 28 districts and 1 city. The sample was taken using the purposive sampling method, with the condition that districts and cities in Aceh Province provide Regional Government Financial Reports (LKPD) for 2016-2019 which provide an overview of the development of Regional Original Income, Balancing Funds, Other Legitimate Income and Expenditures. capital every year. The analytical method used to test the hypothesis is Multiple Linear Regression. The results of this study indicate that Local Goverment Revenuehas a positive effect on Fiscal Stress , Balance Fund has a negative effect on Fiscal Stress , Others Legitimate income has no effect on Fiscal Stress and Capital Expenditures have a negative effect on Fiscal Stress. Several local governments have different characteristics, so they need their own strategies to increase local revenues